The challenges and benefits associated with residential investment in South Africa: residential REIT and portfolio manager perspectives - Van Straaten, Kevin (University of the Witwatersrand, Johannesburg, 2023)
A common theme in addressing critical housing shortages is the call to leverage private sector resources using REITs. Despite South African having critical affordable housing shortages, REIT exposure to residential is far below the global REIT market average. Existing research brings to light the mixed views and perceptions between different stakeholders about the challenges and risks associated with residential REITs. This is exacerbated by the lack of input from managers of residential REITs and residential funds which is critical to establish a more in depth understanding of the characteristics of the sector. The purpose of this research was to understand the challenges faced, methods to overcome these challenges, and the unique benefits that residential investment offers from the perspectives of managers of residential REITs and large scale residential rental portfolios in South Africa. This was achieved using a qualitative survey consisting of semi-structured interviews with managers and executives of residential REITS and large scale residential rental portfolios. The findings provide a more granular look at some of the challenges faced by these key stakeholders, which provide a deep insight into the characteristics of the sector. The key finding is that the limited track record of residential REITs is cause for many of the challenges associated with residential investment in South Africa. Residential portfolio and REIT managers are implementing unique strategies to respond to some of challenges that arise in the context of South Africa such as a shift toward month-to-month leases and exploring methods of reducing utility costs which are increasing at above inflationary rates. These findings make a valuable contribution to the limited literature on residential REITs in South Africa and include insights from the stakeholders that are most acquainted with the sector which is key to helping broaden our understanding of the challenges and benefits of residential investment in South Africa. Understanding these characteristics is crucial in further developing and growing the residential REIT sector which has the potential to help leverage private sector resources to address the critical housing shortages in South Africa and Africa.
A research report submitted in partial fulfilment of the requirements for the degree Master of Master of Science to the Faculty of Engineering and the Built Environment, School of Construction Economics and Management, University of the Witwatersrand, Johannesburg, 2023
Keywords: REIT market; Residential funds; Residential investment; UCTD